Archival Interventions and Disentangling Legacy Records - Cook, Sarah (Archivaria, 2021)
Appraisal and disposition of government records at Library and Archives Canada (LAC) focuses primarily on acquiring the “right” records to best document a given function of the Government of Canada. Once records pass into LAC’s care, access is provided through an inconsistent approach of online descriptive records and on-site finding aids, often with minimal or incorrect contextualizing information that hinders their overall discoverability and use. Through a study of both the legacy photographic records in the National Film Board of Canada Fonds and the recontextualization project currently underway at LAC, the author examines the history of the record, from recordkeeping practices to the transfer to LAC, and some of the interventions by the archives to describe and shape these records over several generations of custodial care. All of these various actions have had a hidden impact on the use and understanding of both the individual records and the larger collection. This article provides a case study in how rearrangement based on research into creators, organizational recordkeeping systems, and archival custodial practices can draw out complex, multiple provenances and provide researchers with a fuller contextual history of the record. RÉSUMÉ L’évaluation et la disposition des documents gouvernementaux à Bibliothèque et Archives Canada (BAC) visent principalement à acquérir les « bons » documents pour mieux documenter une fonction donnée du gouvernement du Canada. Une fois les documents confiés à BAC, l’accès est offert par une approche non uniforme de fiches descriptives en ligne et d’instruments de recherche sur place, souvent accompagnés d’informations contextuelles minimales ou incorrectes qui nuisent à leur découverte et à leur utilisation. En étudiant à la fois les documents photographiques du Fonds de l’Office national du film du Canada et le projet de recontextualisation actuellement en cours à BAC, l’auteure étudie l’histoire des documents, depuis les pratiques de tenue de documents jusqu’au transfert à BAC, et certaines des interventions des archives pour décrire et façonner ces documents sur plusieurs générations de travail de gestion de la collection. Toutes ces actions ont eu une incidence cachée sur l’utilisation et la compréhension des documents individuels et de la collection dans son ensemble. Cet article présente une étude de cas qui montre comment un réarrangement fondé sur des recherches sur les créateurs, les systèmes de tenue de documents des organisations et les pratiques de conservation des archives peut faire ressortir des provenances complexes et multiples et fournir aux chercheurs une histoire contextuelle plus complète du document.